Analisis Pengukuran Kinerja Rumah Sakit dengan Pendekatan Balanced Scorecard (Studi Kasus pada RSUD Pandan Arang Boyolali) - Rahmawati, Risna Aulia; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
The purpose of this research is to measure the performance of RSUD Pandan Arang Boyolali employed the concept of performance measurement that not only measuring financial performance but also financial non namely Balanced Scorecards which includes financial perspective, perspective customers, internal business perspective, perspective and learning and growth. By the use of Balanced Scorecards expected the hospital can develop financial aspects and non in assessing the performance of financial, it is expected that the hospital capable of being institutions that can give satisfaction to the consumers . This research using motode case studies by taking data for 3 years, namely from year 2012-2014. This study was intended to obtain data relating to the measurement the performance of a company that employed the concept of balanced scorecards. Sample in this research is 100 employees and patients RSUD Pandan Arang Boyolali, while for the sample collection using methods simple random sampling. This research result indicates that in general the performance of the RSUD Pandan Arang Boyolali in a position quite seen both from the perspective of a four Balanced Scorecard.